Benthic megafauna and CO2 bubble dynamics observed by underwater photography during a controlled sub-seabed release of CO2. (July 2015) - Kita, Jun; Stahl, Henrik; Hayashi, Masatoshi; Green, Tammy; Watanabe, Yuji; Widdicombe, Stephen
Highlights: We analyzed the responses of megafauna and bubble streams to the CO2 release experiment. No discernible adverse effect by the CO2 release was observed for the megafaunal behavior. Multi-dimensional scaling analysis illustrated natural seasonal shifts in megafauna. The intensity and presence of the CO2 bubble plume was affected by the tidal cycle. Abstract: In 2012, a controlled sub-seabed release of carbon dioxide (CO2 ) was conducted in Ardmucknish Bay, a shallow (12 m) coastal bay on the west coast of Scotland. During the experiment, CO2 gas was released 12 m below the seabed for 37 days, causing significant disruption to sediment and water carbonate chemistry as the gas passed up through the sediment and into the overlying water. One of the aims of the study was to investigate how the impacts caused by leakage from geological CO2 Capture and Storage (CCS) could be detected and quantified in the context of natural heterogeneity and dynamics. To do this underwater photography was used to analyze (i) the benthic megafaunal response to the CO2 release and (ii) the dynamics of the CO2 bubble streams, emerging from the seabed into the overlying water column. The frequently observed megafauna species in the study area were Virgularia mirabilis (Cnidaria), Turritella communis (Mollusca), Asterias rubens (Echinodermata), Pagurus bernhardus (Crustacea), Liocarcinus depurator (Crustacea), and Gadus morhua (Osteichthyes). No discernable abnormal behavior was observed for these megafauna, in any of the zones investigated, during or after the CO2 release. Time-lapse photography revealed that the intensity and presence of the CO2 bubble plume was affected by the tides, with the most active bubbling seen at low tides and the larger hydrostatic pressure at high tide suppressing CO2 bubbling from the seabed.